Analysis of manoeuvres and scoring in competitive surfing - Lundgren, L.; Newton, R. U.; Tran, T. T.; Dunn, M.; Nimphius, S.; Sheppard, J. (International Journal of Sports Science and Coaching, 2014)
In competitive surfing, the choice of, and ability to perform different manoeuvres are crucial for the score outcome. Summarised information about manoeuvres, their frequency and scoring could help coaches and athletes to make the right decisions regarding which manoeuvre to choose, if conditions allow, during a competition heat. All waves from the quarter-finals and up during the World Championship Tour 2012 were analysed in regards to performed manoeuvre and score received. Reentries were the most common manoeuvre, but aerial manoeuvre waves and tube rides scored higher with an average wave score of 7.40±1.53 and 6.82±2.13 respectively, compared to other lower risk manoeuvres that scored an average of 5.08±2.21 (p<0.001). Consequently, the high-scoring manoeuvres had lower completion rate (~50-60% as compared to ~90%). It was concluded that, high performance surfing athletes should be able to execute risk-taking manoeuvres in addition to having a high completion rate on traditional manoeuvres in competition.